ANALISIS KEPUASAN SEKOLAH MITRA TERHADAP MAHASISWA PRAKTIK LAPANGAN KEPENDIDIKAN FKIP UMMY TAHUN 2023 - Hana Adhia; Redo Andi Marta; Helvita Roza; Risza Dwiputri; Roza Zaimil; Ikhwan (LPPM Universitas Ekasakti, 2024)
This research analyzes the level of satisfaction of partner schools towards Educational Field Practice (PLK) students by using a qualitative descriptive research method with a percentage formula. The focus of the research is the results of the analysis carried out at partner schools on PLK students for the Odd Semester 2023/2024, Faculty of Teacher Training and Education, Universitas Mahaputra Muhammad Yamin. The research framework relies on the foundation of thoughts, ideas and policies in the 2022 PLK guidebook. There are 21 partner schools for PLK, consist of 11 SMP/MTSN, 9 SMA/SMK/MAN and 1 Islamic boarding school in Solok City and Regency. Comprehensive analysis of the data shows that the results of the partner schools satisfaction survey for Educational Field Practice students on the student ethics was found at very satisfied percentage (89%), on the communication skills was obtained at satisfied percentage (86%), on the ability to use technology was also at satisfied percentage (86%), on the cooperation ability was obtained at very satisfied percentage (89%), om self-development was fpund at satisfied percentage (85%), and on teaching competence was obtained at satisfied percentage (81%). Thus, based on the indicators, in can be concluded that PLK students are favored by many respondents. This will have an impact on the progress of schools, tutors and PLK students through organizing PLK activities.